How Close is God? How is God Close? Methodology in Liturgical Theology - O'Regan, James (Université Saint-Paul / Saint Paul University, 2013)
This dissertation proposes a direct access, omnidimensional methodology to account for all sensible data sets found in a liturgical event. With the reintroduction of the vernacular to Roman Catholic liturgy in 1968, liturgical theology has attempted to establish a methodology to analyze nonverbal/dynamic data as well as texts. While limited advances were made, there was difficulty in abandoning text-based analyses. In this research, we propose an event-based methodology that can directly account for all physical data sets, based on the five senses. It uses a single language to discuss all kinds of liturgical data and sources of liturgical data. It also allows the liturgical event and its data to remain intact as dynamic phenomena. The methodology, which is called proximity analysis, asks two questions of any aspect of a live-liturgy: how close is X to Y, and how is X close to Y? In this way, anything that can be seen, heard, felt, smelt or tasted can be discussed as close, using a single language to cover multiple data sets. We establish that the theory of proximity was implicit in the literature and successfully apply it in six ways: description, interpretation, criticism, prediction, prescription and management. In the applications, we discover three working theories about speech. Proximity is demonstrated as a useful methodology for examining the literature and live liturgy. We predict that proximity will be a robust and useful tool for determining and executing research projects, for historical or live event endeavours. Further, we predict that proximity will provide best practice for liturgical formation that answers the call for an event-based solution to doing liturgy.
Keywords: Liturgy; methodology; live event; paradigm shift; sound-value; optimal timing; orthologia; correct speech; non-verbal analysis; dynamics analysis